Comparison of multiple modulation techniques for various topologies of multilevel converters for single phase AC motor drive - Laith M. Akram Alsaqal; Ahmed M. T. Ibraheem Alnaib; Omar Talal Mahmood (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
There are various types of Multilevel Converters (MCs) in addition to various types of modulation techniques for these types of MCs; the challenges in selecting the best one of them with regard to the amount of the required of components, and its harmonics content. So, a comparison study among these types has been done in this paper. For comparison study, the simulation of seven level of two popular topologies of MCs: Neutral Point Clamped (NPC) converter, and Cascaded-MCs were carried out with Matlab/Simulink software program. These converters are used to drive a single phase capacitor start motor drive. Multicarrier modulation control techniques are used for controlling the MCs; these techniques involve two main type: Level Shifted Carrier (LSC), and Phase Shifted Carrier (PSC). The comparison is made with respect to the performance factors as, the amplitude of  the Total Harmonic Distortion (THD), and the DC-bus utilization performance which measured by Root Mean Square of the output voltage Vrms at variable modulation indices and variable carrier frequency. Based on simulation results it's found, that the cascaded-MC with PSC modulation method gives best results, in addition to the Alternative Phase Opposition Disposition APOD-LSC modulation technique (with even number of modulation frequency) generate the output voltage with a lower harmonic content compared with the other techniques.